1971
DOI: 10.1021/i160039a011
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Membrane Permeabilities Using a Rotating Batch Dialyzer

Abstract: The rotating batch dialyzer, an exceptionally simple cell for measuring membrane permeabilities, has been characterized in terms of boundary layer permeabilities for six solutes diffusing through Cuprophane. An empirical expression was obtained for calculating boundary layer permeabilities from known values for the rotational speed of the cell, the density and viscosity of the solutions, and the diffusion coefficient of the solute in solution. Permeabilities determined with the rotating cell were confirmed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1974
1974
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The overall mass-transfer coefficients and the corresponding flow rates are given in Table 1. Good agreement was observed with values given by Wendt et al, 1971 (where they used the notation Pobs for overall mass transfer coefficients). During the experiments the same flow rates were used on both sides of the membrane, and consequently Equation (1) (Malone and Anderson, 1977) becomes:…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The overall mass-transfer coefficients and the corresponding flow rates are given in Table 1. Good agreement was observed with values given by Wendt et al, 1971 (where they used the notation Pobs for overall mass transfer coefficients). During the experiments the same flow rates were used on both sides of the membrane, and consequently Equation (1) (Malone and Anderson, 1977) becomes:…”
Section: Resultssupporting
confidence: 77%
“…The permeability of Cuprophan PT-150 to NaCl at 37OC was found to be 1.51 x cm s-l. This value is 50% higher than that given by Wendt et al (1971) even after temperature correction (see Colton et al, 1971). This difference could be attributed to the considerable permeability variation between batches of Cuprophane PT-150 membranes (Hsu et al, 1976).…”
Section: Ar Ozduralmentioning
confidence: 59%
See 1 more Smart Citation
“…The maximum available volume in each compartment was 46 cm3, and the area of exposed film, measured across contact with the large O-ring (100 mm diameter), was 78.5 cm2. Wendt et al (1971) found that the entire measured area of the membrane should be used to calculate observed permeabilities (P") even though the cell is only partly filled. Apparently, the diffusion process continues due to a thin film of solution being carried over the arc above the solution during rotation of the cell.…”
Section: Methodsmentioning
confidence: 99%
“…When a strong alkali, such as sodium hydroxide, was used in place of ammonia, we found the films to be much more transparent and quite permeable to small molecules. Permeability characteristics of the films were measured with a rotating dialysis cell prepared as described by Regan et al (1968) and Wendt et al (1971).…”
Section: Introductionmentioning
confidence: 99%